Antibacterial Activity of Selected Fractions Extract of Coptis chinensis Franch Rhizomes (Medico Legal Update, 2020)
The antibacterial activity of different fractions of selected extract of Coptis chinensis Franch rhizomewas evaluated on gram positive bacteria. Three extracts were tested at concentrations ranging from 1 mg/ml, 10 mg/ml, and 100 mg/ml in vitro on three bacterial strains, Staphylococcus aureus, Streptococcus pneumoniae, and Bacillus anthracis, which was done by performing disc diffusion for growth inhibition. Themethanol extract at concentrations of 100 mg/ml displayed the most significant zone of inhibition of (22.67± 3.055mm), (21.67 ± 3.512 mm), (16.67 ± 1.528 mm) against Streptococcus pneumoniae, Staphylococcus aureus, and Bacillus anthracis, respectively. The TLC separation of the extracts showed that each of them maycontains constituents that are phenolic in nature. From the Rf values of the spots found in the various extractsis that the Coptis chinensis Franch rhizome contains some other non-phenolic compounds responsible for itseffect. The selected methanol extract is then subjected to column chromatography and collected 4 fractions.Out of the four fractions, F2 fraction demonstrates the most significant zone of inhibition of 15.00 ± 1.000mm, 12.33 ± 1.528 mm and 10.00 ± 2.000 mm against Streptococcus pneumoniae, Staphylococcus aureus,and Bacillus anthracis, respectively.